Memories of a Theoretical Physicist A Journey across the Landscape of Strings, Black Holes, and the Multiverse - Polchinski, Joseph (The MIT Press, 2022)
A groundbreaking theoretical physicist traces his career, reflecting on the successes and failures, triumphs and insecurities of a life cut short by cancer. The groundbreaking theoretical physicist Joseph Polchinski explained the genesis of his memoir this way: "Having only two bodies of knowledge, myself and physics, I decided to write an autobiography about my development as a theoretical physicist." In this posthumously published account of his life and work, Polchinski (1954-2018) describes successes and failures, triumphs and insecurities, and the sheer persistence that led to his greatest discoveries. Writing engagingly and accessibly, with the wry humor for which he was known, Polchinski gives theoretical physics a very human face. Polchinski, famous for his contributions to string theory, may have changed the course of modern theoretical physics, but he was a late bloomer-doing most of his important work after the age of forty. His death from brain cancer at sixty-three cut short a career at its peak. Working on the memoir after his diagnosis, using a text-to-speech algorithm because he could no longer read words on a page, he was able to recapitulate his entire career, down to the details of problems he had worked on. For Polchinski, physics went deeper than words. This edition includes photographs from Polchinski's professional and family life, as well as physics explainer boxes, other technical edits, and bibliographic notes by his former student Ahmed Almheiri, a foreword by Andrew Strominger, and an afterword by his wife Dorothy Chun and sons Steven and Daniel.